Predictors of surgical approach for the management of renal cell carcinoma: a population‐based study from New South Wales. Issue 11 (9th June 2016) - Patel, Manish I.; Strahan, Stephen; Bang, Albert; Vass, Justin; Smith, David P.
Abstract : Background: The simultaneous adoption of laparoscopy and partial nephrectomy (PN) has been reported to result in unintended consequences. We aim to examine the contemporary (2001–2009) trends in use of PN and laparoscopy within a population‐wide database. Methods: All renal cell carcinomas diagnosed between 2001 and 2009 in New South Wales, Australia, were identified from the Central Cancer Registry. Records of treatment were electronically linked. All patients with localized renal cell carcinoma who underwent surgical treatment were selected for this study (3771 patients). Follow‐up was to the end of 2010. Multivariable logistic regression analysis was used to determine predictors of PN and laparoscopy. Results: In the entire cohort, 150 (4%), 495 (13%), 1516 (40%) and 1610 (43%) received laparoscopic PN, open PN, laparoscopic radical nephrectomy (RN) and open RN, respectively. Between the years 2001 and 2009, there was a gradual increase in the use of PN except between 2005 and 2007. Between 2001 and 2009, a rapid uptake of laparoscopy was observed. Multivariable analysis demonstrated that age (OR: 0.99 (0.98–0.99)), year of surgery (OR: 1.15 (1.11–1.19)), comorbidity (OR: 1.40 (1.12–1.76)) and hospital case load >8/year (OR: 2.39 (1.49–3.81)) predicted use of PN. Year of surgery (OR: 1.19 (1.15–1.21)), comorbidity (OR: 0.70 (0.58–0.85)), non‐teaching hospital (OR: 0.70 (0.53–0.93)), private hospital (OR: 1.86 (1.45–2.38)) and hospital case load > 8/year (OR: 3.36 (2.22–5.09)) predicted use of laparoscopy. Conclusion: The unintended decrease in PN associated with increased use of laparoscopic RN had reversed by 2009. Hospital case load predicts the use of PN and laparoscopy.